2022
DOI: 10.1007/s41365-022-01037-7
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond time-resolved X-ray ferromagnetic resonance measurements at Shanghai synchrotron radiation facility

Abstract: An experimental picosecond time-resolved X-ray ferromagnetic resonance (TR-XFMR) apparatus with a time resolution of 13 ps (RMS) or 31 ps (FWHM) was constructed and demonstrated in the 07U and 08U1A soft X-ray beamlines at the Shanghai Synchrotron Radiation Facility (SSRF) using pump-probe detection and X-ray magnetic circular dichroism (XMCD) spectroscopy. Element and time-resolved ferromagnetic resonance was excited by continuous microwave phase-locking of the bunch clock within the photon beam during synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…6,16–18 Since then, several alternative synthetic routes have also been published (Scheme 1). 19–21 The more recent syntheses proceed via an amine alkylation rather than a reductive amination as in the original patents. 22 For example, in the patent by Dong and Tang, 6-bromohexanol (Scheme 1a) was acylated with 2-hexyldecanoic acid 2 using catalytic 4-methylbenzene-1-sulfonic acid (TsOH) to yield 7 in 76% yield, enabling a di-alkylation of 4-aminobutanol to produce ALC-0315 in 87% yield (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,16–18 Since then, several alternative synthetic routes have also been published (Scheme 1). 19–21 The more recent syntheses proceed via an amine alkylation rather than a reductive amination as in the original patents. 22 For example, in the patent by Dong and Tang, 6-bromohexanol (Scheme 1a) was acylated with 2-hexyldecanoic acid 2 using catalytic 4-methylbenzene-1-sulfonic acid (TsOH) to yield 7 in 76% yield, enabling a di-alkylation of 4-aminobutanol to produce ALC-0315 in 87% yield (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…22 For example, in the patent by Dong and Tang, 6-bromohexanol (Scheme 1a) was acylated with 2-hexyldecanoic acid 2 using catalytic 4-methylbenzene-1-sulfonic acid (TsOH) to yield 7 in 76% yield, enabling a di-alkylation of 4-aminobutanol to produce ALC-0315 in 87% yield (Scheme 1d). 19,22 Saadati et al recently reported the same synthetic approach, albeit with different conditions for the acylation (86%) and amine di-alkylation (55%) (Scheme 1b and e). 23 Yet another amine-alkylation approach starts with the alkylation of 2-hexyldecanoic acid 2 with 1,6-dibromohexane (Scheme 1c) to yield 7 in 85% yield, with the subsequent amine di-alkylation yielding ALC-0315 in 56% yield (Scheme 1f).…”
Section: Introductionmentioning
confidence: 99%